Predation of nymphal tomato potato psyllid, Bactericera cockerelli (Šulc) (Hemiptera: Triozidae), by the predatory mite, Anystis baccarum L. (Trombidiformes: Anystidae). Issue 2 (2nd July 2016) - Geary, I. J.; Merfield, C. N.; Hale, R. J.; Shaw, M. D.; Hodge, S.
ABSTRACT: This study investigated predatory behaviour of the mite Anystis baccarum on nymphs of the tomato potato psyllid Bactericera cockerelli . In 30-minute laboratory bioassays, predation rates per individual mite were low if late instar psyllid nymphs were 'braced' or 'sealed' tightly to a leaf, with only one nymph from twelve being successfully attacked and eaten in the presence of psyllid sugars (wax covered honeydew). However predation rates were approximately six times higher if the nymph was detached from the leaf and inverted. The presence of psyllid sugars had an impact on predation rates because mites would probe or investigate, and often feed from these sugars, sometimes leading to the immediate cessation of the mite's investigation of the psyllid. Overall, the results of this investigation confirm that these mites consume late instar psyllid nymphs but may need to be at high densities before substantial reductions in psyllids occurred. The mites may be a more effective predator of psyllid eggs or younger instars and this predatory behaviour warrants further investigation.